2015
DOI: 10.1155/2015/830567
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Exercise on Health-Related Fitness, Endotoxin, and Immune Function of Postmenopausal Women with Abdominal Obesity

Abstract: This study was conducted to examine the effects of combined exercise on health-related fitness, endotoxin concentrations, and immune functions of postmenopausal women with abdominal obesity. 20 voluntary participants were recruited and they were randomly allocated to the combined exercise group (n = 10) or the control group (n = 10). Visceral obesity was defined as a visceral-to-subcutaneous fat ratio ≥0.4 based on computed tomography (CT) results. Body composition, exercise stress testing, fitness measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Endotoxins have been considered to be one of the main factors contributing to occupational lung diseases and organic dust toxic syndrome (Park et al, 2015). In fact, changes in pulmonary function due to endotoxin exposure have been (Paudyal et al, 2011), dairy workers (GM: 329 EU/m 3 (Mitchell et al, 2015), animal feed and grain workers (GM: 662 EU/m 3 ), and sewage treatment plant workers (GM: 214 EU/m 3 ) (Cyprowski et al, 2015).…”
Section: Endotoxinsmentioning
confidence: 99%
“…Endotoxins have been considered to be one of the main factors contributing to occupational lung diseases and organic dust toxic syndrome (Park et al, 2015). In fact, changes in pulmonary function due to endotoxin exposure have been (Paudyal et al, 2011), dairy workers (GM: 329 EU/m 3 (Mitchell et al, 2015), animal feed and grain workers (GM: 662 EU/m 3 ), and sewage treatment plant workers (GM: 214 EU/m 3 ) (Cyprowski et al, 2015).…”
Section: Endotoxinsmentioning
confidence: 99%
“…This is supported by Mylsidayu and Moraes that an increase in weight training occurs within 2-6 weeks with the DNLP linear periodization program with 20 reps and 50% of weight using bench press, leg press, front lat pull-down, leg extensions, military press, seated leg curls, pulley triceps extensions, abdominal crunches, and arm curls significantly increased bench press 15RM (175 and 219%), leg press 15RM (395 and 455%), maximal oxygen consumption (VO2 max) (9 and 10%), and free fat mass (2.8 and 3%) [13,14]. Whereas Park said that a combination of aerobic exercise in the form of running with 40% -75% MHR and weight training with 60% -70% 1 RM [15], with 8-10 reps and 3 sets can significantly increase grip strength, push-ups, and intake maximum oxygen (VO2max) [16]. Showed that the application of specific strength training programs can improve the performance capabilities of volleyball player skills.…”
Section: Resultsmentioning
confidence: 99%
“…Various airborne Gram-negative bacteria produce lipopolysaccharides (LPS) with hyper pro-inflammatory and toxic properties (Tirsoaga et al, 2007;Armstrong et al, 2013). These lipopolysaccharides (endotoxins) have been regarded to be one of main cause of both occupational lung diseases and organic dust toxic syndrome (Park et al, 2015). Mitchell et al (2015) reported changes in pulmonary function due to endotoxin exposure in dairy workers.…”
Section: Discussionmentioning
confidence: 99%